Nitrogen use efficiency and expression of nitrogen transporter of upland rice - Mohd Amin, Adibah; Abdul Rahman, Zaharah; Musa, Mohamed Hanafi; Abdullah, Siti Nor Akmar (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
Nitrogen (N) is one of the most yield restraining nutrients for upland rice production. The objectives of this study are to determine the nitrogen use efficiency (NUE) of upland rice landraces and to identify the expression of high-affinity ammonium transporter that is expressed under different nitrogen level. The first study focused on the effect of P fertilization on NUE of upland rice. Five landraces of upland rice seedlings were transplanted in plots treated with 0kg P/ha and 100kg P/ha. The 15N source is from 15N labelled ammonium sulphate fertilizer [15(NH4)2SO4] with 1% 15N atom excess. Landrace III had the highest NUE which was 52.59%. There were no significant effects on NUE, DMY and grain yield caused by P fertilization. The second experiment on the expression of high-affinity ammonium transporter was carried on two upland rice landraces that showed the highest and lowest NUE from previous experiment. Plants were treated with modified Yoshida nutrient solution with 0.05mM NH4NO3, 0.1mM NH4NO3, 1mM NH4NO3 and 2mM NH4NO3. The expression of ammonium transporter (OsAMT1;1) was observed. Landrace III had the highest expression, thus supporting the results that landrace III had significantly higher NUE.